Pelatihan Manajemen Stres pada Penderita Penyakit Kronis di Kelurahan Beringin Semarang - Rahayu Winarti; Machfud Saifudin; Meirita Pranawati; Raidha Febria Handayani; Wahyu Griyaningsih; Tri Dian Herlambang Sakti; Niken Sukesi; Wahyuningsih Wahyuningsih (Compromise Journal Community Proffesional Service Journal, 2023)
Stress can worsen disease and reduce quality of life in patients with chronic diseases. This is because a chronic illness that is suffered for a long time will disrupt all aspects of life, including financial problems, career, role disorders, and including psychosocial problems. The aim of this community service is to increase the knowledge and abilities of chronic disease sufferers regarding stress management through training activities.The results of a preliminary study through interviews with cadres, residents and community health center officers show that mental health services are not yet optimal, especially for people with chronic illnesses. People, especially those suffering from chronic diseases, do not yet know about stress management techniques and there is no special program from the Community Health Center for health services for patients experiencing psychosocial problems. Health services are only provided to patients with serious mental disorders. The activity method used to overcome the problem is 1) Education through counseling to community groups suffering from chronic diseases and about psychosocial problems such as stress and ways to reduce and overcome it. 2) Training and Demonstration, after being given education through partner counseling, demonstrations of deep breathing and muscle relaxation are given. 3) Evaluation to determine the extent of the program's success and to ensure the sustainability of the program. Evaluation activities will be carried out using instruments to measure the partner's level of knowledge and skills. Activities continued with consolidation with the community health center and village government for the sustainability of the mental health service program, including the psychosocial early detection program.The results of the education were that participants' knowledge about stress management increased by almost 95%, participants were able to carry out deep breathing and progressive muscle relaxation techniques independently and stated their attitude that they would apply them at home.